A new manifestation of thrombocytopenia: myocardial haemorrhage with symptomatic arrhythmia. Issue 8 (August 1982) - Wyld, PJ; Beck, S; Slater, DN
Abstract : We describe a patient with thrombocytopenia who developed episodes of dyspnoea due to recurrent cardiac arrhythmia. Necropsy revealed that the apparent mechanism was extensive myocardial haemorrhage.